A Review of Data Quality Assessment: Data Quality Dimensions from User’s Perspective - Ruzaini, Abdullah Arshah; Mohd Zafrol, Abdullah (American Scientific Publisher, 2018)
High quality data is an important asset in numerous business and organizations. The quality of data, i.e., the ability of data to meet user requirement can have a tremendous impact in an organization to develop an astounding data quality satisfaction subsequently provide a better platform to achieve top service in organizations. The assessment of data quality dimensions must consider the degree to which data satisfy users’ needs. Data quality assessment although multi-dimensional but identical in most of the assessment structure. Therefore, it is important to develop an assessment of data quality dimensions specifically to measure the degree of user’s satisfaction and judgement of the data to obtain a correct interpretation of data quality assessment result. This paper proposes a conceptual framework of data quality assessment from user’s perspective that draws the assessment specifically to measure user requirements and satisfactions. This framework can be evaluated and will be used to improve and extend knowledge of relationship between data quality dimensions and its assessment from user’s perspective.